2016
DOI: 10.1002/ijc.30225
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of recurrence and treatment in male breast cancer: A clue to prognosis?

Abstract: Male breast cancer (MBC) patients seem to have inferior survival compared to female (FBC) ones, which is not fully explained by usual prognostic factors. Recurrence analysis could show differences in relapse patterns and/or in patients' approaches that justify these outcomes. Retrospective analysis of MBC patients treated in a cancer center between 1990 and 2014, looking for relapse. For each patient, three matched FBC patients were selected by: diagnosis' year, age (within 5 years), stage and tumors' type (on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…At present, it is believed that it is mainly lack of awareness of breast cancer in male patients or delays in diagnosis that might be the cause of this phenomenon. 7,18,19 A study found that only 29% of 100 Croatian MBC patients were diagnosed 20 In addition, Hong and colleagues suggested that the prolonged period of symptom duration of MBC was also the reason for the difference in the rate of distant metastasis between MBC and FBC patients, 17 and NI and colleagues' study of 64 cases of male breasts without breast cancer showed columnar cell changes in 39 cases (61%), which was considered to be a transitional stage in the development of some low-grade ductal carcinoma in situ and invasive breast cancer. 21 In our opinion, in addition to the above reasons, differences in gene mutation may also cause this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…At present, it is believed that it is mainly lack of awareness of breast cancer in male patients or delays in diagnosis that might be the cause of this phenomenon. 7,18,19 A study found that only 29% of 100 Croatian MBC patients were diagnosed 20 In addition, Hong and colleagues suggested that the prolonged period of symptom duration of MBC was also the reason for the difference in the rate of distant metastasis between MBC and FBC patients, 17 and NI and colleagues' study of 64 cases of male breasts without breast cancer showed columnar cell changes in 39 cases (61%), which was considered to be a transitional stage in the development of some low-grade ductal carcinoma in situ and invasive breast cancer. 21 In our opinion, in addition to the above reasons, differences in gene mutation may also cause this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Whether there is a difference in prognosis compared with FBC is debatable. A poorer outcome has been indicated in several studies 6 8 , but also similar 9 , 10 or even better prognosis than FBC 11 have been reported. Studies on genomic and transcriptional levels have demonstrated molecular differences between MBC and FBC.…”
Section: Introductionmentioning
confidence: 54%
“…Male breast cancer is a rare condition that can have higher mortality compared to the female equivalent [ 2 , 8 ]. Male breast cancer has unique characteristics that differ from their female counterparts.…”
Section: Discussionmentioning
confidence: 99%